A study on the adequacy of the anti-trafficking in persons act 2007 in protecting trafficked children in Malaysia / Nurul Ain Ibrahim, Intan Nor Nadhirah Ismail and Khazan Baktiah Muhammad Asrinani. - Ibrahim, Nurul Ain; Muhammad Asrinani, Khazan Baktiah; Ismail, Intan Nor Nadhirah (Faculty of Law, 2010)
This study attempts to analyze the adequacy of the Anti-Trafficking in Persons Act 2007 in giving protection to trafficked children. Provisions of the Anti-Trafficking in Persons Act 2007 with regards to the trafficked children are discussed and scrutinized in order to identify weaknesses that are apparent. Its adequacy in protecting the trafficked children and the sufficiency of the punishments provided to those involved in the trafficking of children are examined thoroughly. The study would emphasise certain treaties such as the Convention on the Rights of the Child, the Protocol to Prenvent, Suppress and Punish Trafficking in Persons, Especially Women and Children Supplementing the United Nations Convention Against Transnational Organized Crime and the ASEAN Declaration Against Trafficking in Persons Particularly Women and Children 2004, all relating to children trafficking, which Malaysia has acceded. It is the objective of this study to analyze and scrutinize existing laws and efforts that has been made by the Government, to ensure that they comply with the treaties acceded by them. The study would also discuss the efficacy and efficiency of the enforcement officers dealing with the trafficking of children. Methods such as semi-structured interviews, library research and online researches were carried out in order to complete the research. Upon completion of doing so, this study will propose suggestions and reformations where it deemed necessary.